Molecular characterization of Plasmodium falciparum DNA-3-methyladenine glycosylase - Nattapon Pinthong; Paviga Limudomporn; Jitlada Vasuvat; Poom Adisakwattana; Pongruj Rattaprasert; Porntip Chavalitshewinkoon-Petmitr (Malaria Journal, 2020)
Abstract Background The emergence of artemisinin-resistant malaria parasites highlights the need for novel drugs and their targets. Alkylation of purine bases can hinder DNA replication and if unresolved would eventually result in cell death. DNA-3-methyladenine glycosylase (MAG) is responsible for the repair of those alkylated bases. Plasmodium falciparum (Pf) MAG was characterized for its potential for development as an anti-malarial candidate. Methods Native PfMAG from crude extract of chloroquine- and pyrimethamine-resistant P. falciparum K1 strain was partially purified using three chromatographic procedures. From bio-informatics analysis, primers were designed for amplification, insertion into pBAD202/D-TOPO and heterologous expression in Escherichia coli of recombinant PfMAG. Functional and biochemical properties of the recombinant enzyme were characterized. Results PfMAG activity was most prominent in parasite schizont stages, with a specific activity of 147 U/mg (partially purified) protein. K1 PfMAG contained an insertion of AAT (coding for asparagine) compared to 3D7 strain and 16% similarity to the human enzyme. Recombinant PfMAG (74 kDa) was twice as large as the human enzyme, preferred double-stranded DNA substrate, and demonstrated glycosylase activity over a pH range of 4–9, optimal salt concentration of 100–200 mM NaCl but reduced activity at 250 mM NaCl, no requirement for divalent cations, which were inhibitory in a dose-dependent manner. Conclusion PfMAG activity increased with parasite development being highest in the schizont stages. K1 PfMAG contained an indel AAT (asparagine) not present in 3D7 strain and the recombinant enzyme was twice as large as the human enzyme. Recombinant PfMAG had a wide range of optimal pH activity, and was inhibited at high (250 mM) NaCl concentration as well as by divalent cations. The properties of PfMAG provide basic data that should be of assistance in developing anti-malarials against this potential parasite target.